A concept of materialism and well-being - Asa Ismia Bunga Aisyahrani; Lina Handayani; Maya Kusuma Dewi; Mastura Mahfar (Institute of Advanced Engineering and Science, 2020)
Materialism is related to financial individuals who judge all things need material. The nature of people like this exist in today's era, which assesses a success comes from the acquisition of wealth, social status and welfare of life. Although this is contrary to moral life, there are still many people who pursue it. Internal and external factors exist in human life related to the existence of materialism. Self satisfaction and individual life goals are internal factors that exist within the individual. Materialistic people will feel satisfied through acquisition of possessions, financial success, attaining status and having the right image. This perception is negatively correlated with well-being, even so they believe that their life goals will be achieved through materialism. Environmental, social and social media influences that are external factors in an individual can provide a tendency to influence one's behavior. The recognition of social status based on wealth will have an impact on materialism that will be difficult to escape from his life. The hedonist lifestyle and corruption are the effects of this growing materialism. However, to prevent or overcome these behavioral problems, it is necessary to strengthen morality and spiritual values that can be obtained from various sources such as the Qur'an, the Bible or research that can be trusted to provide solutions to these problems.